Information literacy in the context of startups - Ottonicar, Selma Leticia Capinzaiki (2021)
Startups are organizations that focus on information technologies, and they are generally composed of few organizational individuals, and there is a natural tendency to value innovation. With this aim, that is, to innovate and build ‘new’ knowledge, professionals need skills and abilities to access and analyze reliable information. Information literacy contributes to the access to information to be efficient, resulting in effective decision making. The objective is to investigate the relevance of information literacy for the learning of professionals who work in startups and to propose a model for the application of this competence in a startup accelerator. The methodological procedures involve bibliographic research on information literacy in the business area and startups that made it possible to build a model of insertion of this competence for accelerated startups. The results demonstrate that knowing how to evaluate and add value to knowledge is essential for startups to innovate and acquire competitive advantage. The final considerations emphasize that the model of insertion of information literacy can be inserted in the accelerator of startups, promoting innovation and knowledge from consistent and reliable information. This accelerator can promote information competence through training courses and workshops with specialists in the field.